AKIBAT HUKUM ATAS PENYITAAN OBYEK JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN - Wijaya, Happy Trizna (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Consumer finance companies often take the action of taking objects that are used as fiduciary collateral when the debtor is unable to repay the loan. This was done because the consumer finance institution did not register the fiduciary guarantee with the Fiduciary Office. By not registering fiduciary guarantees, the fiduciary guarantee institution does not get a fiduciary guarantee certificate in which there is a clause of the sentence